Application of lean manufacturing in reducing cycle time in the cylinder head component at PT TM - Zuhair, Afiy Haekal; Safariyani, Eva; Wahyudin, Wahyudin (Operations Excellence: Journal of Applied Industrial Engineering, 2025)
The manufacturing industry continues to grow with intense competition, so companies need to improve efficiency and reduce waste in the production process. Lean Manufacturing with Kaizen approach is one of the effective methods to optimize workflow and reduce waste. PT TM faces problems in the production process, especially in the post 2 packing component cylinder head, where there are cycle time fluctuations that have an impact on production efficiency. To overcome these problems, the Lean Manufacturing method with Kaizen approach is applied to reduce waste and improve production efficiency. This study aims to analyze the effect of Kaizen implementation in reducing cycle time and identifying waste that occurs in the production process. The methods used include direct observation in the production line, data collection and analysis, and implementation of Kaizen-based improvements. The results showed that the implementation of Kaizen succeeded in reducing cycle time from 97 seconds to 80 seconds, with a takt time of 105 seconds. In addition, two types of waste were found, namely waiting for 25 seconds and motion for 6 seconds, which have been minimized through changes in layout and work procedures. The conclusion of this study is that the Kaizen method is effective in improving production time efficiency and reducing waste.